PEMBERDAYAAN KELUARGA DALAM PERAWATAN LANSIA YANGMENDERITA HIPERTENSI DI KELURAHAN SRI MERANTI - Arneliwati, Arneliwati; Zulfitri, Reni; Agrina, Agrina; Herlina, Herlina; Sabrian, Febriana; Dwiguna, Stephanie; Aziz, Ari Rahmat (INSTITUT KESEHATAN DELI HUSADA, 2024)
Hypertension is one of the diseases experienced by many elderly people in Indonesia. This disease is often overlooked because it does not show obvious symptoms in the early stages, but if not treated properly, hypertension can cause serious complications such as heart disease, stroke, and kidney disorders. The management of hypertension in the elderly often requires support from the family for regular monitoring and lifestyle changes. This community service program aims to empower families in caring for the elderly suffering from hypertension in Sri Meranti Village, Pekanbaru City, through socialization, blood pressure monitoring training, and distribution of blood pressure monitoring devices. The results showed a significant increase in family knowledge about hypertension management, skills in monitoring blood pressure, and family awareness of the importance of healthy lifestyle changes for the elderly.